2019
DOI: 10.1109/tdei.2019.008155
|View full text |Cite
|
Sign up to set email alerts
|

Modeling oil-paper insulation frequency domain spectroscopy based on its microscopic dielectric processes

Abstract: The present study sets out to devise a universal function model to explain the characteristic curve obtained in the frequency domain spectroscopy (FDS) test on oil paper insulation, based on its microscopic conduction and relaxation processes, and thus to enhance the accuracy and applicability of the test. First, from the analysis of the relationship between the real and imaginary parts of the dielectric's complex permittivity, it is demonstrated that a relaxation peak co-exists with the conduction process in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…It is presented that the ε *( ω ) processed by LD could also form an obvious ‘peak’ in low‐frequency regions by using oil‐paper insulation. In literature [24], the temperature effect on LDS itself is analysed, which is based on another original formula for LD calculation. Further, if the polarisation information can be extracted in the research, the observed results are interesting and deserve further attention.…”
Section: The Theoretical Basis Of Complex Relative Permittivitymentioning
confidence: 99%
See 1 more Smart Citation
“…It is presented that the ε *( ω ) processed by LD could also form an obvious ‘peak’ in low‐frequency regions by using oil‐paper insulation. In literature [24], the temperature effect on LDS itself is analysed, which is based on another original formula for LD calculation. Further, if the polarisation information can be extracted in the research, the observed results are interesting and deserve further attention.…”
Section: The Theoretical Basis Of Complex Relative Permittivitymentioning
confidence: 99%
“…Given these issues, an alternative idea is reported to extract the polarisation information from the total FDS data by using logarithmic‐derivative spectroscopy (LDS). In the current work, the LDS of oil‐paper insulation is first calculated by using the logarithmic‐derivative (LD) method [23, 24]. Findings revealed that the mathematical formula for extracting the polarisation information can be derived using LDS.…”
Section: Introductionmentioning
confidence: 99%
“…Take this as a reference, Figure 6 reveals each peak's accumulated charge quantities QTSDC under different bias voltages. According to [21], it could be inferred from Figure 6 that the QTSDC of Relaxation A remains positive and is in a linear correlation with the bias voltage amplitude; this indicates that Relaxation A is dominated by a dipole. Meanwhile, the QTSDC of Relaxation C changes from positive to negative when the bias voltage turns to positive, the variation law of which is consistent with electrode polarization.…”
Section: Experimental Data From Sample's Tsdc Measurementmentioning
confidence: 92%
“…Meanwhile, the QTSDC of Relaxation C changes from positive to negative when the bias voltage turns to positive, the variation law of which is consistent with electrode polarization. As regards Relaxation B, the relationship between its accumulated charge quantity and According to [21], it could be inferred from Figure 6 that the Q TSDC of Relaxation A remains positive and is in a linear correlation with the bias voltage amplitude; this indicates that Relaxation A is dominated by a dipole. Meanwhile, the Q TSDC of Relaxation C changes from positive to negative when the bias voltage turns to positive, the variation law of which is consistent with electrode polarization.…”
Section: Experimental Data From Sample's Tsdc Measurementmentioning
confidence: 96%
“…In recent years, the frequency dielectric spectroscopy (FDS) method has been widely used in evaluating the insulation condition of cables, due to its advantage of non-destructive [6][7][8][9]. Wang et al [10] performed FDS measurement on 10 kV XLPE cable with different ageing conditions under 200 V testing voltage.…”
Section: Introductionmentioning
confidence: 99%